Influence of Employment on Economic Growth in Sub-Saharan Africa. Does Financial Stability Matter? - Lambon, Justice Iddrisu; Ocansey, Evans O. N. D.; Ababio, Opoku Kwaku (International Journal of Finance, 2025)
Purpose: The primary objective is to determine whether employment significantly influences economic growth and how financial stability, alongside other macroeconomic variables, affects this relationship. Methodology: To achieve this, the study employs a robust quantitative design using panel data from 38 SSA countries covering the period from 2000 to 2023. The analysis utilizes the Generalized Method of Moments (GMM) technique, which controls for endogeneity, unobserved heterogeneity, and autocorrelation, ensuring the credibility of causal inferences. Findings: Empirical results reveal that employment, financial stability and education attainment significantly enhance economic growth at these coefficients and p-values (β = 0.0025, p < 0.01), (β = 0.3587, p < 0.001), (β = 0.00497, p < 0.001) respectively. However, credit to private sector and inflation are negatively associated with economic growth respectively at these coefficients and p-values, (β = -0.00077, p < 0.01), and (β = -0.00079, p < 0.001). Notably, the interaction between employment and financial stability is negative (β = -0.0073, p < 0.01), implying that while both independently support growth, financial stability may inadvertently weaken the impact of employment, likely due to constrained credit flow to high-employment informal sectors. Unique Contribution to Theory, Practice and Policy: These findings carry critical implications for policymakers, emphasizing the need to balance financial sector resilience with inclusive employment strategies. The study also highlights the role of education and inflation control in driving sustainable development. Finally, it calls for a re-evaluation of financial intermediation frameworks to ensure they promote employment-led growth without compromising macroeconomic stability.